Croatia on the FDI market - Tihomir Janjiček (Ekonomski Vjesnik, 2000)
Foreign direct investments have a great impact on any national economy. They contribute to economic growth and bring modern technology into the national economy. After political democratization and economic liberalisation in Central and Eastern European countries, many of them manifested deficiency of capital for investments in the national economies. Geographically, Croatia is located in the region of Central Europe. Croatia has shown intention to be a member of the European Union. Unfortunately, Croatia nowadays is not included with other countries from the region of Central Europe and Eastern Europe in a program of unification to EU. However, Croatia is included in the package with Bosnia and Herzegovina, Yugoslavia, Macedonia and Albania. All these countries are treated as a Western Balkan group and they are not included in any program of unification with EU. Even Romania and Bulgaria have much better chances to be included in EU sooner than Croatia. The Croatian government’s “economic” explanation for this fact is due to a lack of interest of foreign investors for Croatia. The question is: is the amount invested by foreign investors through foreign direct investments really significantly smaller in Croatia than in other Central and East European countries? That is why it is necessary to research how foreign investors targeted often Croatia? What is the position of Croatia on the world FDI market compared with other Central and Eastern European countries? First of all, the main characteristics of FDI need to be examined.